Freedom of Expression and Its Implications for Citizens' Constitutional Rights Following Constitutional Court Decision No. 36/PUU-XX/2022 - Eza Tri Yandy; M. Al Fathoni; Sayuti; Tri Endah Karya Lestiyani (Candela Edutech Indonesia, 2026)
The judicial review of Law No. 11 of 2008, as amended by Law No. 19 of 2016, to the Constitutional Court was filed by twenty-nine content creators as petitioners, who felt that their constitutional rights had been violated by the enactment of Article 27 paragraph 3 and Article 28 paragraph (2) of the Electronic Information and Transactions Law, as they often give rise to multiple interpretations and are not in accordance with democratic principles in the concept of the rule of law. The purpose of this study is to determine how freedom of expression is regulated in the Indonesian legal system and its implications following Constitutional Court Decision Number 36/PUU-XX/2022. The method used in this study is normative legal research with a case approach. After analyzing the data sources obtained, this study concludes that in the context of the rule of law, freedom of expression is a fundamental right possessed by every individual and recognized universally. In a constitutional state, this freedom is guaranteed by the Constitution, as stated in Article 28E paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Freedom of expression serves to monitor and criticize those in power, maintain accountability, and encourage innovation and social progress. In addition, the Constitutional Court's decision has caused harm and/or negative impacts on democracy in Indonesia, including a decline in the democracy index, legal uncertainty, and losses in implementation.